Enhancing IT Hybrid Projects in The Directorate General Of Customs And Excise of Indonesia: An Improvement Process - Nugraha, Tito Febrian; Raharjo, Teguh; Wibowo, Wahyu Setiawan; Syahnuddin, Bob Hardian (The Indonesian Journal of Computer Science, 2024)
The Directorate General of Customs and Excise (DJBC) confronts mounting challenges due to the expanding international trade. To address this issue, an optimal software solution is required for efficient service provision and supervision of transactions. However, the completion of IS projects faces significant delays, with only 25% reaching completion despite the immediate need for a reliable system. These delays stem from various problems encountered during project execution. This research employs the Kerzner Project Management Maturity Model to assess the IS project management maturity level at DJBC and categorise the identified problems. Subsequently, solutions extracted from PMBOK 7 are mapped to address these issues. Findings indicate an average maturity score of 390, falling short of the target of 600 required for level 1 maturity. Additionally, 13 problems have been identified and linked to solutions within the seven standards/domains of PMBOK 7. The research presents two strategic goals: improving project management processes and enhancing client satisfaction, assessed using seven measurement indicators. This study offers valuable insights for DJBC to address project management challenges, enhance maturity levels, and achieve desired outcomes.